Developing speed and agility for sports performance - Jeffreys, I.; Goodwin, J. E. (Strength and conditioning for sports performance, 2016)
The expression of speed and agility is central to many types of athletic performance. At their simplest, speed can be considered to be the ability to complete movements rapidly with respect to time, whereas agility implies the capacity to do so with control. Considering this, all sports skills invoke varying demands for the expression of both qualities. Unlike locomotive speed, which has a clear mechanical definition (distance/time), agility is a more difficult fitness variable to accurately define [18], largely because of the highly context-specific nature of agility performance. Movement in sport is concerned with allowing the athlete to maximise his/her sports performance, and all actions must ultimately allow the athlete to optimally express the specific sport skills required of a given situation In this way, agility is ultimately both sport-specific and task-specific, with the athlete aiming to optimise the performance of a task within the overall sports context. Agility can therefore be broadly defined as efficient and controlled facilitative movement allowing optimised integration with sport-specific skills, reduced injury risk and maximised performance. This definition includes the perceptual and cognitive aspect of performance that must be integrated with the physical aspects in athletic settings [20]. Maximal running speed, movement speed and agility are outcomes of acceleration and therein are determined by the pattern of force production and ultimately impulse accumulation under sport-specific time constraints. Strategies to enhance the magnitude and effective application of movement-specific force production capabilities come from considering the factors creating those time constraints and also those limiting force production. A constraints model of skill development [22] can be helpful in exploring the factors limiting performance and understanding where the strength and conditioning (S&C) coach can have a positive impact upon the developmental process. For the development of speed and agility in a game context a number of factors can be identified and have been classified here into three types [1 5].